2009
DOI: 10.1016/j.biocontrol.2009.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of an acarine pest by single and multiple natural enemies

Abstract: Biological control of an acarine pest by single and multiple natural enemies Cakmak, I.; Janssen, A.R.M.; Sabelis, M.W.; Baspinar, H. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…We found no significant differences when multiple predatory species were released to control TSSM numbers when compared with the release of P. persimilis alone. Schausberger and Walzer (2001) reported a similar situation with P. persimilis and N. californicus when released to control of Tetranychus cinnabarinus Boisduval on gerbera plants, and Cakmak et al (2009) found that the control of this species on strawberries was not improved when these two species were released together. TSSM suppression varied among crop phases being proportionally greater in the early crop phase in both years.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found no significant differences when multiple predatory species were released to control TSSM numbers when compared with the release of P. persimilis alone. Schausberger and Walzer (2001) reported a similar situation with P. persimilis and N. californicus when released to control of Tetranychus cinnabarinus Boisduval on gerbera plants, and Cakmak et al (2009) found that the control of this species on strawberries was not improved when these two species were released together. TSSM suppression varied among crop phases being proportionally greater in the early crop phase in both years.…”
Section: Discussionmentioning
confidence: 77%
“…Multiple natural enemy releases have been employed as a way to improve pest suppression also in strawberries Cakmak et al, 2009;de Menten, 2011;Rahman et al, 2011). However, using multiple species may enhance or may reduce pest control, and there is no general agreement on whether the use of single or multiple biocontrol agents is economically profitable and beneficial for pest management (Gerson and Weintraub, 2007;Chow et al, 2010;Onzo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have documented that several predatory mites were effective in control of T. urticae (Rhodes and Liburd 2006; Fraulo and Liburd 2007; Cakmak et al 2009). However, other reports indicated that the use of some predator species as biological control agents had low efficacy in control of T. urticae on vegetable crops (Opit et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the long term, in collaboration with the International Institute of Tropical Agriculture (IITA), the predator Phytoseiulus longipes Evans could be introduce as a biological control agent against T. evansi (Ferrero et al, 2011). Multiple natural enemy releases have been employed as a way to improve pest suppression (Yaninek et al, 1998;Hanna and Toko, 2001;Onzo et al, 2003;Yaninek and Hanna, 2003;Rhodes et al, 2006;Cakmak et al, 2009;Rahman et al, 2011; Azand em e-Hounmalon, pers. com.).…”
Section: Discussionmentioning
confidence: 98%